Institutionelle Lerngelegenheiten und bildungswissenschaftliches Wissen angehender Lehrkräfte – Ergebnisse einer Studie zur Wirksamkeit des bildungswissenschaftlichen Studiums in Bachelorstudiengängen. - Watson, Christina; Seifert, Andreas; Schaper, Niclas (Lehrerbildung auf dem Prüfstand)

Comparison of terminally ill cancer- vs. non-cancer patients in specialized palliative home care in Germany – a single service analysis. - Stiel, Stephanie; Heckel, Maria; Seifert, Andreas; Frauendorf, Tobias; Hanke, Roland Martin; Ostgathe, Christoph (BioMedCentral Palliative Care)

Evaluation der Einführung des Praxissemesters am Standort Paderborn – Konzeption und erste Ergebnisse. - Seifert, Andreas; Festner, Dagmar (1. Internationaler Kongress „Lernen in der Praxis)

Alignment to the Actions of a Robot - Vollmer, Anna-Lisa; Rohlfing, Katharina; Wrede, Britta; Cangelosi, Angelo (International Journal of Social Robotics)
Alignment is a phenomenon observed in human conversation: Dialog partners' behavior converges in many respects. Such alignment has been proposed to be automatic and the basis for communicating successfully. Recent research on human-computer dialog promotes a mediated communicative design account of alignment according to which the extent of alignment is influenced by interlocutors' beliefs about each other. Our work aims at adding to these findings in two ways. (a) Our work investigates alignment of manual actions, instead of lexical choice. (b) Participants interact with the iCub humanoid robot, instead of an artificial computer dialog system. Our results confirm that alignment also takes place in the domain of actions. We were not able to replicate the results of the original study in general in this setting, but in accordance with its findings, participants with a high questionnaire score for emotional stability and participants who are familiar with robots align their actions more to a robot they believe to be basic than to one they believe to be advanced. Regarding alignment over the course of an interaction, the extent of alignment seems to remain constant, when participants believe the robot to be advanced, but it increases over time, when participants believe the robot to be a basic version.
Keywords: learning; Human-robot interaction; Alignment; Robot social; Action understanding

Gesturing in joint bookreading - Rohlfing, Katharina; Grimminger, Angela; Nachtigäller, Kerstin (Learning from Picturebooks)

Entstehung multimodaler Sprachlehrstrategien in spezifischen Interaktionen - Grimminger, Angela; Rohlfing, Katharina (Lernen durch Vorlesen. Interdisziplinäre Beiträge aus Forschung und Praxis)

Becoming a participant: shaping infants’ dialogical actions in repeated interactions - Nomikou, Iris; Rohlfing, Katharina; Rączaszek-Leonardi, Joanna

Constructing interaction: the development of gaze dynamics - Nomikou, Iris; Leonardi, Giuseppe; Rohlfing, Katharina; Rączaszek-Leonardi, Joanna

Early action words - Nomikou, Iris; Rohlfing, Katharina; Cimiano, Philipp; Mandler, Jean

Grammatik. Studikurs im Bereich Sprach- und Textverständnis. - Topalović, Elvira; Dünschede, Susanne; Droste , Pepe

Earenfight, Theresa: Queenship in Medieval Europe - Foerster, Anne (Das Mittelalter)

Dijital Emek ve Karl Marx - Fuchs, Christian

Culture and Economy in the Age of Social Media - Fuchs, Christian

Reconsidering Value and Labour in the Digital Age

Zur Theoriebildung und Analyse der digitalen Arbeit. Die globale Produktion digitaler Hard- und Software (Teil I) - Fuchs, Christian (Z 103)

Internet, Kapitalismus und periphere Entwicklung im Waldviertel - Fuchs, Christian (Momentum Quarterly – Zeitschrift für sozialen Fortschritt (Journal for Societal Progress))

Internet, Capitalism, and Peripheral Development in the Waldviertel - Fuchs, Christian (New Proposals)

Towards a Theoretical Model of Social Media Surveillance in Contemporary Society - Fuchs, Christian; Trottier, Daniel (Communications: The European Journal of Communication Research)

The Macbride Report in Twenty-First-Century Capitalism, the Age of Social Media and the BRICS Countries - Fuchs, Christian (Javnost: The Public)

Power in the Age of Social Media - Fuchs, Christian (Heathwood Journal of Critical Theory)